Grundtvig til undervisningsbrug - Michelsen, William (Grundtvig-studier, 1973)
Grundtvig for teaching purposes.N. F. S. Grundtvig: Tre Danne-Virke-artikler. Aarhus 1972. Studieserien, published by the Danish Teachers’ Association: Grundtvig og det folkelige (by Marianne Ju h l Christiansen and Lise Ettrup), Organisme tanken (by Aage Henriksen) and Tværsnit 1870 (by Peter Søby Kristensen). Copenhagen 1972 and 1973. Reviewed by W illiam Michelsen. These booklets show that it is not only Grundtvig’s best-known hymns and poems which are used for teaching purposes, but also the prose he wrote as a critic and a speaker. In the booklet about Grundtvig and the people, there is furthermore a definition of the idea of »det folkelige« (what pertains to the people), which accords with Grundtvig’s own ideas and which is supported by the texts that follow, which also include his imitators and critics.There is no doubt at all that Grundtvig regarded the people - the individual nation - as a living organism developing in a comparable manner to the individual human being. In this respect he was a romantic and can - in a way – be counted among the thinkers who suscribed to the »organism idea«, as Aage Henriksen expresses it. But when this idea is traced back to Spinoza and carried forward to Hegel, Marx and Freud, one must nevertheless protest against Grundtvig - along with Henrich Steffens and Paul Diderichsen - being the only Danish representative, from whose works a passage is quoted (from October 1810 – see Grundtvig-Studier 1956). He was in reality (from December 1810) an opponent of the whole of this school of thought, apart from in his acceptance of the idea of the people as an organism.